Valis: A Quintessentially Phildickian Novel - Jakovljević, Mladen M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The journey of the protagonist of Philip K. Dick’s novel Valis across different personalities, points in time, and realities becomes a penetrating exploration of the very fabric of the real through his heteromorphic cosmogony that can serve as a paradigm to understanding Dick’s literary-philosophical matrix. Whether a diagnosis or a profound insight into other realities, both insanity and schizophrenia in Valis develop into a means to diagnose the nature of reality by projecting the microcosm of an individual to the macrocosm of the entire universe and vice versa. Dick’s earlier major works of fiction are reflected in Valis as is Valis reflected in them in a way that shows that the line between insanity and reason, and reality and hallucinations, is not only thin but often non-existent. Unlike many who consider themselves normal, Dick never recoiled from an opportunity to embark on an exploration of other realities, both in life and in his fiction, as is evident from the close and intimate connections among them.
Keywords: schizophrenia; insanity; perception; reality; Philip K. Dick; multiverse; science fiction